Effects of Selenium-Enriched Yeast on Performance, Egg Quality, Antioxidant Balance, and Egg Selenium Content in Laying Ducks - Zhang, Xiufen; Tian, Lu; Zhai, Shuangshuang; Lin, Zhenping; Yang, Huiyong; Chen, Junpeng; Ye, Hui; Wang, Wence; Yang, Lin; Zhu, Yongwen (Frontiers in Veterinary Science, 2020)
This study investigated the effects of dietary selenium-enriched yeast (SY) supplementation on the performance, egg quality, plasma antioxidant status, and egg selenium (Se) content in laying Longyan ducks. A total of 480 32-week-old ducks were randomly divided into four dietary treatments, each consisting of six replicates of 20 ducks. The treatments were a basal diet (0.15 mg Se/kg) and three diets corresponding to three supplementation levels of Se (0.05, 0.15, and 0.25 mg Se/kg) via SY into the basal diet. Dietary SY supplementation did not affect either laying performance or egg quality (p > 0.05) but it improved the antioxidant status of ducks, as inferred by greater GSH-Px and CAT activities, and decreased their MDA content in plasma (p < 0.05). The Se contents in yolk, albumen, and whole egg increased linearly as dietary Se levels increase. With more feeding days, the Se contents in yolk and whole egg from non-SY-supplemented ducks increased linearly(p < 0.05), while those from SY-supplemented ducks showing a quadratic relationship (p < 0.05). The Se deposition in the whole egg from ducks fed diets with 0.15 and 2.5 mg Se /kg from SY peaked on day 13 and 12 of the feeding trial, respectively. In conclusion, dietary SY supplementation was able to enhance the plasma antioxidant status and extent of Se deposition in laid eggs. We thus recommend that dietary supplementation of 0.15 or 0.25 mg Se/kg via SY for 13 or 12 days is beneficial for producing Se-enriched eggs in laying ducks.